Development of Augmented Reality-Based Flashcard Media In Science Class Viii Junior High School - Shindy Aulia Febbiola; Septriyan Anugrah; Reni Kurnia; Alkadri Masnur (International Journal of Science and Environment (IJSE), 2026)
This study aimed to develop an Augmented Reality (AR)-based flashcard learning media for the Human Digestive System topic for eighth-grade students at SMP Kartika 1-7 Padang and to evaluate its validity, practicality, and effectiveness. The research employed the Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants included one material expert, two media experts, six students in the small-group trial, and 31 students in the field implementation. Data were collected through validation sheets, student response questionnaires, and learning achievement tests in the form of pretests and posttests. The results indicated that the media achieved a validity score of 93.33% from the material expert and an average of 92.86% from the media experts, both categorized as highly valid. The practicality score reached 97.56%, categorized as highly practical. The effectiveness was demonstrated by an increase in the average score from 65.16 to 88.58 and an N-Gain value of 0.71 (high category). Therefore, the AR-based flashcard media is valid, practical, and effective in improving students' conceptual understanding.